Różne spojrzenia na proces intercepcji drzew i jego determinanty - Klamerus-Iwan, Anna (Leśne Prace Badawcze, 2014)
The subject of the study is the process of interception by plants defined as the process of retaining rainfall water on plant surface, counting retention by individual plant parts or the vegetation cover as the whole. In the quantitative approach, interception capability of plants may be compared to a reservoir, the capacity of which is determined mostly by the surface of plants. Among many approaches to describe interception processes, a lot of attention has been focused on research concerning the forest vegetation with reference to atmosphere – forest stand – soil balance. Hence, in the present paper interception issues are addressed in view of forest ecosystems. The emphasis is also put on the methods and results of studies carried out under laboratory conditions. Up-to-date literature on interception is abundant. The authors tackling this issue regularly define their own variable and complex sets of terms. This paper is an attempt to review and organize knowledge presented in existing literature on the subject.